Learning from genetic blood disorders: A systematic review of digital educational strategies to improve adherence in thalassemia care - Rosalia Ratri Wulandari; Wastu Adi Mulyono (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Adherence to lifelong treatment is a critical challenge for patients with thalassemia and other hereditary blood disorders. Educational and digital interventions have emerged as promising strategies to strengthen patient self-management and adherence. Purpose: To systematically review the effectiveness of digital and educational interventions in improving adherence, self-efficacy, and psychosocial outcomes among patients with thalassemia and other hereditary blood disorders. It also sought to identify the role of nursing-led digital programs in supporting patient empowerment and long-term treatment engagement. Method: This systematic review followed PRISMA 2020 guidelines. Comprehensive searches were conducted in PubMed, Scopus, and Web of Science for studies published between 2010–2025. Eligible studies included RCTs and quasi-experiments evaluating educational or digital interventions to improve adherence and self-efficacy in patients with thalassemia, sickle cell disease, or hemophilia. Results: Ten studies met the inclusion criteria, showing that mobile health (m-Health), e-learning, and telenursing programs significantly improved adherence, disease knowledge, and self-efficacy compared with standard education.Conclusion: Educational and digital interventions are effective adjuncts to conventional care in promoting adherence among patients with thalassemia. This systematic review provides insights into integrating digital health strategies in nursing practice.